Identifying the Relationship between Students Computer Hardware Skills in the Use of Electronic Information Resources in University Libraries in South-West, Nigeria - Sambo, Atanda Saliu; Akanwa Precious, Pearl C (International Journal of Knowledge Content Development & Technology, 2022)
This study determined relationship between students’ computer hardware skills in the use of electronic information resources in University libraries in South-West, Nigeria. This study adopted correlation research design involving simple and multiple linear methods. The population of this study is 85,526. The sample for the study was 398. Proportionate sampling techniques were used to draw the sample. The findings revealed that there is a moderate positive and significant relationship between the students’ computer hardware skills and their use of EIR in university libraries. Also, there is a moderate positive and significant relationship between the students’ computer software skills and their use of EIR in university libraries in South- West, Nigeria; and there is a high and significant relationship among students’ computer hardware skills, computer software skill and their use of electronic information resources in the university library in South-West, Nigeria. Based on the above findings, the study recommended among others that undergraduate students should enhance their computer hardware skills since it is related with the use of electronic information resources in the universities. Research implications were also offered.